METHODOLOGY OF STANDARDIZING THE QUALITY IN SUBURBAN BUS TRANSPORT AND ITS APLICATION IN SLOVAKIA – TOTAL APPROACH (Perner's Contacts, 2015)
The article deals the standardization of the quality level in suburban bus transport in the total approach. The procedures respect the legislative requirements which are valid in the Slovak Republic. There are applied the proposed methods to specific measurement results of expectation and perception of the quality of the passengers with the help of service quality loop. The results are objectified with the measurements of controllers in a significant transport hub of northern Slovakia. This approach is not yet applied in the Slovak Republic.